Regional Collaborations as a Way Forward for Maternal, Newborn and Child Health: The South Asian Healthcare Professional Workshop - Requejo, Jennifer H; Toure, Kadidiatou; Bhutta, Zulfiqar; Katz, Imtiaz; Zaidi, Shahida (Journal of Health, Population and Nutrition, 2010)
This article reviews the importance of regional initiatives in the context of global efforts to achieve the Millennium Development Goal 4 and 5 and describes the action-oriented multi-country healthcare professional association (HCPA) workshops organized by the Partnership for Maternal, Newborn and Child Health. The South Asian HCPA workshop served as a catalyst for strengthening the ability of HCPAs in South Asian countries to organize and coordinate their activities effectively, play a larger role in national planning, and collaborate with other key stakeholders in maternal, newborn and child health. Key words: Capacity-building; Child health; Child welfare; Healthcare associations; Maternal health; Maternal welfare; Neonatal health; Regional collaboration; Workshops; Asia, South DOI: 10.3329/jhpn.v28i5.6149 J HEALTH POPUL NUTR 2010 Oct;28(5):417-423